Estudo das propriedades químicas e antimicrobianas de soluções de hipoclorito de sódio em diferentes concentrações - Tomasi, Gisele (2013)
The aim of this study was to evaluate the chemical and antimicrobial properties of sodium hypochlorite solutions at different concentrations before and after contact with Enterococcus faecalis. Different concentrations of sodium hypochlorite solution (0.5%, 1%, 2.5% and 5.25%) were exposed to the pathogen for 30 minutes, 20 minutes, 10 minuntes and 15 seconds respectively. The antimicrobial activity of the solutions was evaluated using the agar diffusion test. Freshly manipulated and resulting NaOCl solutions were placed inside wells prepared on agar plates. After the incubation period, the inhibition of bacterial growth formed around the wells were measured with the aid of digital calipers. The hydrogen potential of the solutions was measured by digital pH meter. Was also performed to quantify the amount of active chlorine and chloramines from initial and resulting solutions. It was found that the residual hypochlorite solutions showed no statistically significant difference in relation to antimicrobial activity and pH.Regarding the active chlorine content, the resulting solutions decreased at all concentrations. Chloramines were not found in any of the solutions tested. It was concluded that, at the time intervals tested, the physicochemical properties of the residual NaOCl were not changed, except the amount of free chlorine.